2020
DOI: 10.3390/ijgi9100594
|View full text |Cite
|
Sign up to set email alerts
|

PolySimp: A Tool for Polygon Simplification Based on the Underlying Scaling Hierarchy

Abstract: Map generalization is a process of reducing the contents of a map or data to properly show a geographic feature(s) at a smaller extent. Over the past few years, the fractal way of thinking has emerged as a new paradigm for map generalization. A geographic feature can be deemed as a fractal given the perspective of scaling, as its rough, irregular, and unsmooth shape inherently holds a striking scaling hierarchy of far more small elements than large ones. The pattern of far more small things than large ones is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…However, there are still many problems worthy of study in this field. The key is feature extraction, especially automatic feature extraction to reduce manual annotation [13][14].…”
Section: Key Issues Involved In Automatic Synthesismentioning
confidence: 99%
“…However, there are still many problems worthy of study in this field. The key is feature extraction, especially automatic feature extraction to reduce manual annotation [13][14].…”
Section: Key Issues Involved In Automatic Synthesismentioning
confidence: 99%
“…More importantly, they found that the fractality of street networks is positively correlated with urban socioeconomic status and negatively correlated with energy consumption. In another study, Ma et al [22] developed a useful tool, called PolySimp, for simplifying complex polygons based on the underlying scaling hierarchy of polygons. The tool's effectiveness has been demonstrated using British coastline data.…”
mentioning
confidence: 99%